Peningkatan Produksi Semen Ayam Kampung Melalui Suplementasi Daun Kelor (Moringa oleifera) - Heru Suripta; Puji Astuti (Fakultas Pertanian Universitas Veteran Bangun Nusantara Sukoharjo, 2021)
AbstractRural chickens are widely developed by artificial insemination methods, so good quality semen is needed so that fertility and hatching eggs are high. Moringa is famous as a